Unmasking of bacteriophage Mu lipopolysaccharide receptors in Salmonella enteritidis confers sensitivity to Mu and permits Mu mutagenesis. - Müller, K H (1988)
The human pathogen Salmonella enteritidis 3b was found to be highly resistant to phage P22 and Mu derivatives. The Mu sensitivity (musA1) allele from Salmonella typhimurium could be transferred to S. enteritidis 3b at low frequency by cotransduction with hisG::Tn10. Sensitivity to Mu resulted in a large reduction in the number of lipopolysaccharide core-region oligosaccharides that were substituted with O-antigen polysaccharide. The residual high-molecular-weight lipopolysaccharide appeared to be a hybrid displaying O antigens which were immunologically related to those of S. typhimurium and not to those of S. enteritidis. Consequently, Mu d1(Ap lac) could then be transduced into Mus strains forming stable lysogens. On temperature induction, Mu transposition could easily be used to generate mutations in genes coding for cell surface antigens including fimbriae, lipopolysaccharide, and flagella.